CPR - Furey, Rachel (Stone Canoe 16, 2022)
Keywords: dept.eng; literary-work

“Maybe There’s Nobody to Shoot”: The Disappearing Landlord in 20th-Century U.S. Fiction - Stretch, Cynthia (American Houses: Literary Spaces of Resistance and Desire, 2022)
Section: American Houses: Literary Spaces of Resistance and Desire
Keywords: American Studies; General; History; North America; Social Sciences; dept.eng

Explaining Baseball to Kurt Schwitters: Donald Hall’s Philosophy of Mortality in ‘Baseball’ and ‘Extra Innings.’ - Petrie, Paul R. (Modern Language Studies, 2022)
Keywords: dept.eng

The Life and Times of Chinua Achebe - Ogbaa, Kalu (Routledge, Taylor & Francis Group, 2022)
"The Life and Times of Chinua Achebe introduces readers to the life, literary works, and times of arguably the most widely-read African novelist of recent times, an icon, both in continental Africa and abroad. The book weaves together the story of Chinua Achebe, a young Igboman whose novel Things Fall Apart opened the eyes of the world to a more realistic image of Africa, a continent warped by generations of European travelers, colonists, and writers. Whilst continuing to write further influential novels and essays, Achebe also taught other African writers to use their skills to help their national leaders to fight for their freedoms in the post-colonial era, as internal warfare compounded the damage caused by European powers during the colonial era. In this book Kalu Ogbaa, an esteemed expert on Achebe and his works, draws on extensive research and personal interviews with the great man and his colleagues and friends, to tell the story of Achebe and his work. This intimate and powerful new biography will be essential reading for students and scholars of Chinua Achebe, and to anyone with an interest in the literature and post-colonial politics of Africa"–
Keywords: 20th century; Achebe; Chinua; Achebe; Chinua; Biography; Political and social views; Authors; Nigerian; dept.eng; faculty_collection

Should we teach students how to bullshit? - McEachern, Peter J.; McEachern, Robert W. (Writing and Pedagogy, 2022)
Bullshit, as defined by Frankfurt (2005, p. 10), is language that is “disconnected from a concern for the truth.” Much scholarship shows that bullshit is a prominent feature in organizations that is difficult, if not impossible, to get rid of (e.g., McCarthy et al., 2020; Penny, 2010). Bullshit, by definition and by cultural practice, seems antithetical to business writing orthodoxy. As Thill and Bovée (2020) suggest in a representative textbook, communication should be clear and ethical. However, Spicer (2020) codifies bullshit as a social practice whose outcomes are not always dire. Well-crafted bullshit benefits its users, allowing them to “fit into a speech community, get things done in day-to-day interaction and bolster their image and identity” (Spicer, 2020, p. 20). Contrasting with business writing’s abstinence-only bullshit stance, this suggests that successful writers must adapt to their organization’s speech act practices. In this article, we argue that students must be taught about bullshit. After describing bullshit and its role in organizations, we show how business writing could incorporate a critically informed approach to bullshit in undergraduate courses, internship preparation courses, and other curricular instances in which students work directly with organizations. While bullshitting should not be outright encouraged, continued ignorance will do nothing to solve its associated problems. Promoting bullshit literacy, however, could both minimize bullshit’s harms and maximize its benefits. We close by describing how this approach could foster critical thinking skills, promote more seamless adaptation to organizational cultures and communication practices, and perhaps even improve mental health outcomes.
1 citations (Crossref) [2023-10-31]
Keywords: Bullshit; Bullshitology; Business Writing; dept.eng; peer-reviewed

Sea Wolf Meditation - Sonnenschein, Dana (Spoon River Poetry Review, 2022)
Keywords: dept.eng

We Need to Talk About War Metaphors in Oncology - McEachern, Robert W. (JCO Oncology Practice, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.eng

Tea Ceremony - Sonnenschein, Dana (Corvid Queen, 2022)
Water the color of oolong reflects her shape vanishing.
Keywords: dept.eng; ⛔ No DOI found

Nest Robbers - Sonnenschein, Dana (The Curator, 2022)
...
Keywords: dept.eng

Queering Anti-Zionism: Academic Freedom, LGBTQ Intellectuals, and Israel/Palestine Campus Activism - Blackmer, Corinne E. (Wayne State University Press, 2022)
"This book explores the work of five influential pro-BDS (Boycott, Divestment, and Sanctions) queer academic activists-Sarah Schulman, Jasbir Puar, Angela Davis, Dean Spade, and Judith Butler-each of whom exemplify different ideological and critical practices around anti-Zionism"–
Keywords: Boycotts; Foreign public opinion; Israel; Boycott; divestment; and sanctions movement; Zionism; Gay rights; Israel; Israel; Disinvestment; Politics and government; dept.eng; faculty_collection

Bird Guides (poem) - Sonnenschein, Dana (Thimble Literary Magazine, 2022)
Keywords: dept.eng

Lady Macbeth, her book - Sonnenschein, Dana (Embark: A Literary Journal for Novelists, 2022)
A.D. 1034 The king and queen took hawks out that day, and their retinue trailed along hills and swales, watching as Duncan and then Suthen lifted gauntleted arms and opened their fists. The hunting…
Keywords: dept.eng; ⛔ No DOI found